(untitled) (Research, Society and Development, 2022)
Introduction: Ballet Pilates is a way of associating Pilates principles with Classic Ballet movements. The exercises employ body weight as a load, they can be adapted according to physical condition of each one. In a short time of practice, it is possible to observe the results, such as reducing weight, increasing muscle strength and improving posture. Objective: Analyze the muscular strength, flexibility and balance of women who practice Ballet Pilates, comparing them as variables before and after two months of practicing the sport. Methodology: The present study is of intervention and field, of comparative character and quantitative nature. A survey included 14 volunteers practicing the sport, aged 20 to 50 years old, and a data collection was carry out at the Tiradentes University. Data were collect using the Lafayette isometric dynamometer, the Sanny analog fleximeter and the Arkipelago baropodometry platform. Results: According to a strength analysis, muscle gains were observe, especially in the quadriceps, gluteus and calves, with statistical statistics for right quadriceps (p = 0.008) and left gluteus (p = 0.021). In the flexibility variable, differences were observed before and after the activity execution, with positive impact on the following muscle groups: torso (p = 0.004), hip flexors (p <0.001) and hamstrings (p <0.001). No significant difference in balance was find, measured by baropodometry, after two months of performing the Ballet Pilates modality. Conclusion: It was find that the Ballet Pilates modality is capable of promoting muscle strength gain, being observe in the study participants, mainly in the quadriceps and gluteus muscle groups. In addition, it became the flexibility gain exhibited by practitioners of this activity, exerting a positive influence, especially on the torso, hip flexors and hamstrings. As for balance, very expressive results were not observed, due to fact that the students have already presented balance preservation.